ANALYSIS OF THE COMPANY'S FINANCIAL PERFORMANCE BY USING THE ECONOMIC VALUE-ADDED METHOD (EVA) ON PT BANK MUAMALAT INDONESIA TBK - -, Muhammad Mashduqi; Ahmad Ramadhan (ShariaBiz International Journal of Economics & Business, 2025)
This research is motivated by the serious profitability problems faced by Bank Muamalat Indonesia Tbk, this can be seen from the company's net profit which tends to decline. This will affect people's desire to become funding or landing customers, thereby reducing public interest and trust so the problem formulation in this research is how to describe the performance and assess the financial performance of PT Bank Muamalat Indonesia using the Economic Value Added (EVA) method. The aim of this research is to determine the performance description and financial performance assessment of PT Bank Muamalat Indonesia using the Economic Value Added (EVA) method. A theory regarding financial performance that contains a description of the financial conditions that will be used as a benchmark for a company. And the theory regarding the Economic Value Added (EVA) method, there are several steps in calculating EVA, namely calculating Net Operating Profit After Tax (NOPAT), Weighted Average Cost of Capital (WACC), Invested Capital (IC) and Capital Chargers (CC). This type of research is descriptive quantitative. The data collection techniques used in this research are documentation study and literature study. The population in this research is all annual financial reports at PT Bank Muamalat Indonesia, consisting of balance sheets and profit and loss reports which have been distributed on the website www.bankmuamalat.co.id for the 2016-2020 period